RESPON PETANI PADI SAWAH TERHADAP KEBIJAKAN INSENTIF DAN DISINSENTIF DI KOTA TASIKMALAYA, JAWA BARAT - Aprilliza Naura; Lies Sulistyowati; Maman Haeruman Karmana (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
It seems that the incentive and disincentive policies are not yet ideal to make rice farmers control land conversion. This requires the response of farmers to the incentive and disincentive policies that are desired in order to create a match between the wishes of the government and farmers. The purpose of the study was to describe the characteristics of rice farmers and analyze the response of farmers to incentive and disincentive policies. The research method is quantitative research with the number of respondents 206 rice farmers and the proporsionate stratified random sampling technique. The method of analyzing farmers 'characteristics uses descriptive statistical analysis and farmers' responses to incentive and disincentive policies using a Likert scale. The results showed the characteristics of farmers, namely the age of farmers classified as productive age groups; most farmers take education up to elementary school level; farmers have a low income in one growing season, which is Rp. 1,607,000; the majority of farmers are included in the narrow area of arable land area of 0.23 ha; The average number of family dependents is 3 people; in terms of farming experience having sufficient knowledge and experience; and the dominating land status is sakap land. Farmers responses to the incentive and disincentive policies on average farmers strongly agree with the incentive policy and agree with the disincentive policy and the socialization of LP2B which is quite low.